“The border” as a topos in recent Bulgarian literature - Burneva, Nikolina (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2023)
The locus is usually charged with historical semantics, which gives rise to semiotic chains and collective attitudes. The expansion of the term’s semantic valence to include conceptual elements as characteristics of contemporary sociological and psychological markers justifies empathetically memorable interpretations of key complexes of the migrating ego, which e.g. “Border” (2017) by Kapka Kassabova, “East of the West” (2011) by Miroslav Penkov and “Life in the Rocks” (2018) by Maria Laleva revealed. The synergy of narrative and stylistic character is examined from a system-theoretical point of view in order to justify conclusions about current aesthetic and cultural-sociological epistemes: skepticism about civilization, interpretations of the past, individual and collective identity designs. Bulgarian origin and the observer perspective of emigrants – the specifics of this world view(s) are the focus of the study, as life experience of migrating personalities in the currently globalized civilization.